The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pcbi.1005077
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Hypoxia-Activated Prodrugs to Prevent Drug Resistance in Solid Tumors

Abstract: Experimental studies have shown that one key factor in driving the emergence of drug resistance in solid tumors is tumor hypoxia, which leads to the formation of localized environmental niches where drug-resistant cell populations can evolve and survive. Hypoxia-activated prodrugs (HAPs) are compounds designed to penetrate to hypoxic regions of a tumor and release cytotoxic or cytostatic agents; several of these HAPs are currently in clinical trial. However, preliminary results have not shown a survival benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Moreover, some efforts using modeling approaches to investigate the role of the microenvironment in drug resistance have also been conducted recently. For instance, Lindsay and colleagues (22) developed a stochastic model to simulate the effect of oxygen on the growth kinetics of cancer cells and to investigate the potential benefits of combining hypoxia-activated prodrugs with standard targeted therapy to prevent drug resistance in non-small cell lung cancer. In addition, our previous study (23) designed a modeling framework using stochastic differential equations to simulate the therapy-induced microenvironmental adaptation that promotes the growth and metastasis of resistant tumor cells, and therefore contributes to the development of the acquired drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some efforts using modeling approaches to investigate the role of the microenvironment in drug resistance have also been conducted recently. For instance, Lindsay and colleagues (22) developed a stochastic model to simulate the effect of oxygen on the growth kinetics of cancer cells and to investigate the potential benefits of combining hypoxia-activated prodrugs with standard targeted therapy to prevent drug resistance in non-small cell lung cancer. In addition, our previous study (23) designed a modeling framework using stochastic differential equations to simulate the therapy-induced microenvironmental adaptation that promotes the growth and metastasis of resistant tumor cells, and therefore contributes to the development of the acquired drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…A different study reached a similar conclusion with an EGFR targeted agent with a mathematical model showing that longer time under TH-302 therapy without the targeted inhibitor erlotinib allowing the EGFR sensitive cell population to expand drastically due to TH-302 resistance. Optimal schedule of an agent affecting both the hypoxic and normoxic populations may allow for the longest duration of control of the two populations (11).…”
Section: Discussionmentioning
confidence: 99%
“…Another concurrent article used similar mathematical concepts to compare Class I HAPs to Class II HAPs and, furthermore, to determine optimal properties for Class II HAPs [23]. Lindsay et al [32] developed a stochastic model to study monotherapies and combination therapies involving HAPs, specifically TH-302, and erlotinib. Amongst other findings, they concluded that a combination therapy of the two drugs impedes the uprising of drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Lindsay et al . [ 32 ] developed a stochastic model to study monotherapies and combination therapies involving HAPs, specifically TH-302, and erlotinib. Amongst other findings, they concluded that a combination therapy of the two drugs impedes the uprising of drug resistance.…”
Section: Introductionmentioning
confidence: 99%